2013
DOI: 10.1111/arcm.12011
|View full text |Cite
|
Sign up to set email alerts
|

The Source of Iron‐Oxide Pigments Used in Pecos River Style Rock Paints

Abstract: The likely sources of iron-oxide pigments used in prehistoric rock paintings in the Lower Pecos Archaeological Region were identified on the basis of chemical fingerprinting using LA-ICP-MS. The chemical signatures of 13 red rock paint samples collected from two south-west Texas sites were compared with three potential source materials (ochre, siltstone and rhyolite), and two pigment cakes (crayons) that were excavated near the sampling sites. The significant chemical similarities between the paint and siltsto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Furthermore, using LA–ICP–MS, Bu et al . () found that red pictographs in the Lower Pecos contained elevated iron levels.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Furthermore, using LA–ICP–MS, Bu et al . () found that red pictographs in the Lower Pecos contained elevated iron levels.…”
Section: Resultsmentioning
confidence: 96%
“…Many laboratory‐based methods are able to answer more far‐reaching research questions such as sourcing and elemental fingerprinting (cf., Bu et al . ). Below is a list of considerations when conducting handheld pXRF analysis of pictographs.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Bu et al . ) have employed solution or laser ablation ICPMS to measure the trace element composition of ochre pigments. Unlike INAA, which requires up to 6 weeks of decay time after sample irradiation before short, middle and long measurements can be completed, LA–ICPMS yields results that are effectively instantaneous (Pollard et al .…”
Section: Introductionmentioning
confidence: 99%